Absolute adsorption of light hydrocarbons and carbon dioxide in shale rock and isolated kerogen - Wu, Tianhao; Zhao, Huangjing; Tesson, Stéphane; Firoozabadi, Abbas (Fuel (Guildford), 2019)
Natural gas production from shale formations has changed the energy landscape. Knowledge of adsorption in the subsurface shale formations improves resource assessment. The excess adsorption is directly measurable from experiments. Evaluation of fluid content in shale is based on the absolute adsorption. At high pressure relevant to subsurface conditions, the computation of absolute adsorption from excess adsorption has shortcomings when the conventional models are used. In this work, we first present the excess sorption data of light hydrocarbons and carbon dioxide in subsurface shale rock and in isolated kerogen. Gravimetric method was used in our measurements. The results show that, at high pressure, the excess adsorption of ethane and carbon dioxide decreases significantly as pressure increases. Excess adsorption of ethane at 60 °C for the shale sample investigated becomes negative at high pressure. The conventional models may provide a non-monotonic absolute adsorption and even magnify the unphysical negative adsorption. In addition to the proposed model based on adsorbed layer volume, we also account for effective sample volume due to the pore volume accessibility by different molecules, as well as the swelling of kerogen. The adsorption data from subsurface shale and the method for analysis presented in this work set the stage for prediction capability in hydrocarbon production from shale reservoirs.